2022
DOI: 10.3389/fchem.2022.839680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Borax On Sintering Kinetics, Microstructure and Mechanical Properties of Porous Glass-Ceramics From Coal Fly Ash by Direct Overfiring

Abstract: The direct sintering process of coal fly ash for the preparation of glass-ceramics is the liquid-phase sintering process, from non-densification to densification. When the temperature exceeds the densification temperature point, the porosity of glass-ceramics on the contrary increases and the pore diameter increases. This provides a basis to prepare porous glass-ceramics by direct overfiring. Adding borax to coal fly ash can reduce the temperature of liquid phase formation, reduce the preparing temperature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…For instance, Zeng et al prepared porous glass-ceramics through LPS using coal fly ash as raw materials. 14 They found that the addition of borax to the coal fly ash can reduce the temperature of liquid-phase formation and assist densification. However, they did not characterize the where the liquid phase locates after sintering.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zeng et al prepared porous glass-ceramics through LPS using coal fly ash as raw materials. 14 They found that the addition of borax to the coal fly ash can reduce the temperature of liquid-phase formation and assist densification. However, they did not characterize the where the liquid phase locates after sintering.…”
Section: Introductionmentioning
confidence: 99%